AN ANALYSIS OF SOCIOLECT LANGUAGE VARIATION OF SOCIAL INTERACTION IN SURAU LAUIK SOCIETY - intan Juwintan (Program Studi Pendidikan Bahasa Inggris Fakultas ilmu Budaya, 2022)
The language in our daily lives has many kinds of variation. One of those variations is sociolect. Sociolect is language variation related with social and culture. The uniqueness of this research is Minang Language phenomenon used by Surau Lauik society when do the conversations with friends, so the language used is not accordance with the Minang standard. This research aims to identify the types of sociolect language variation used by Surau Lauik society in Panampuang village of Ampek Angkek and the most language variation used by Surau Lauik society. In this research, the writer used qualitative-descriptive method with ethnographic design. The method used to collect data is observation, recording, and transcription. Based on the result of the analysis and discussion, this study shows that sociolect that found in Surau Lauik society are colloquial, slang, jargon, vulgar, and argot. The Most of sociolect language variation found in the data conversation is vulgar, vulgar tends to negative and disrespectful. Vulgar spoken by Surau Lauik society aged 20-30 years and used in unformal situation.